Weighted inequalities for some integral operators with rough kernels - Riveros, María Silvina; Urciuolo, Marta (2022)
Fil: Riveros, Maria Silvina. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.